Multifunctional landscapes for agroecological transition and climate resilience - Kumar, Gopal; Borah, Gulshan; Tripathi, Mansi; Malaiappan, Sudharsan; Sikka, Alok (2026)
Insights from a Special Session at the 6th International Agronomy Congress during 24–26 November 2025 in New Delhi, India. The country, India has successfully moved to the status of a surplus food-producing nation, ensuring overall food availability and stability. However, agriculture now faces multiple and interconnected challenges, including climate change, water scarcity, soil degradation, pest pressure, and low farm incomes. To discuss integrated pathways, a Special Session on “Multifunctional Landscapes” was organized during the 6th International Agronomy Congress, focusing on how agriculture can simultaneously support food production, climate resilience, water security, biodiversity, and livelihoods.